Identification of PTSD in adults with intellectual disabilities in five patients in a specialised psychiatric inpatient unit. Issue 2 (2014) - ,; ,; ,; ,; ,; ,; ,; ,
Abstract : Purpose – The purpose of this paper is to describe and discuss assessment of post‐traumatic stress disorder (PTSD) in adults with intellectual disabilities. Existing research in this area encompasses case studies, and includes, for the most part, persons with mild intellectual disabilities.Design/methodology/approach – The aim of this study is to investigate symptom presentation and subsequent identification of PTSD in persons with more severe intellectual disabilities; i.e. persons with moderate or severe intellectual disabilities. Five patients in a specialised psychiatric inpatient unit for patients with intellectual disabilities were included. Information about the patients was collected through case files and interviews with key informants: family, milieu therapists, and caregivers in community settings, and observations through inpatient admission. The authors of this paper followed a training programme for trauma therapists in addition to the inpatient treatment of the five patients. The five patients all met criteria for PTSD according to the Diagnostic Manual – Intellectual Disability.Findings – Previously, it was not suspected that the five patients suffered from PTSD, although they had experienced terrifying incidents. All patients displayed severe changes in behaviour, which may have overshadowed symptoms of PTSD. PTSD in persons with more severe intellectual disabilities may be interpreted as challenging behaviour, or other psychiatric disorders such as psychosis.Research limitations/implications – The limitation of the study is the small number of participants.Practical implications – Practical implication is linked to clinical practice related to identification of PTSD in persons with intellectual disabilities.Originality/value – The paper may encourage more research into how PTSD can be identified in persons with moderate and severe intellectual disabilities. The case reports may help clinicians to look for traumatic experiences in persons with intellectual disabilities who have experienced terrifying incidents. Acknowledgements : The present study is a result of a training programme for health professionals working in the psychiatric services in Norway, known as Safer Trauma Therapists (in Norwegian: Tryggere Traumeterapeuter (TT)). The authors, who all work in the same specialised psychiatric unit for adults with intellectual disabilities, participated in this programme lasting ten months (rvts.no). The insights from this programme urged the authors to facilitate assessment and interventions towards people with intellectual disabilities who experience post‐traumatic stress disorder, PTSD. The authors are grateful to the five patients and their families for their co‐operation with this study. The authors also wish to thank psychologist Trine Anstorp for her clinical counselling and her encouragement while preparing the manuscript.